Praca zawodowa źródłem nieformalnej edukacji pracowników - Myjak, Teresa (Kultura-Społeczeństwo-Edukacja, 2022)
The aim of the publication is to present professional work as an important source of employees’ education and learning in the workplace, on the example of a selected enterprise operating in the construction industry. The study has both a theoretical and an empirical character. The first part discusses the issues of defining professional work, its importance for a man, and related learning. The second part shows the practices in the field of informal employees’education applied to participants in the work process and their approach to learning in the selected enterprise. The publication uses two methods: literature analysis and case study. The considerations contained in the study may be helpful in understanding the importance and role of nonformal education of employees of enterprises and assessing practices in this area.